Hero’s Journey in Percy Jackson and The Olympians: The Lightning Thief - Aditya Nanda Difa (Passage, 2022)
The study explored the hero’s journey theory by Campbell and how it was used in the story of Percy Jackson. The study aimed to see the development of characters found in the story by using the closereading method and segmentation where sections of the story would be classified into their own segments matching the stages of the hero’s journey. The hero’s journey played a massive role in the story and influenced how the characters developed. The story stayed true to the fundamentals of the hero’s journey theorem and had archetypes of the story that had significant roles. The study can be improved further by analysing the intent of the characters.